Democracy abroad, lynching at home: racial violence in Florida - Hobbs, Tameka B. (University Press of Florida, 2015)
In this book, Tameka Hobbs investigates the history of racial violence and lynchings in Florida, focusing especially on a string of brutal lynchings that occurred during the 1940s. She argues that these lynchings created difficult diplomatic moments during both World War II and the Cold War period and that they forced the U.S. government to become more active in prosecuting racial violence